Introduction - Bernaciński, Łukasz; Łabno, Anna (A thousand years of Poland’s presence among the elite of European states, 2026)
The authors — Anna Łabno and Łukasz Bernaciński — present the publication as an attempt to examine the historical, legal, and constitutional aspects of the millennial anniversary of Poland's first royal coronation, as well as to reflect on its significance for contemporary Poland. The monograph covers several key thematic threads. It discusses Bolesław the Brave's path to the crown in the context of Poland's Christianization initiated by Mieszko I, Polish-German relations as a structural challenge to Polish sovereignty, the contribution of Polish legal thought to the development of international law, as well as the republican and constitutional tradition — including the legal continuity of the Polish state in exile during and after World War II. The authors emphasize that Poland's thousand-year experience of statehood offers valuable lessons for the present day. Preserving sovereignty requires not only military and economic strength, but also a deep rootedness in tradition and an awareness of one's own national identity. For this reason, the conference concluded with a panel discussion devoted to current threats to Poland's sovereignty and its standing in the international arena.